How Do You Comprehend Tahilalats Comic? - Jayaputri, Herlandri Eka (PAROLE: Journal of Linguistics and Education, 2017)
This  study  discusses  the  use  of  the  cooperative  principles  and  the conversational  implicatures  in  Nurfadli  Mursyid’s  Tahilalats  comic. Tahilalats is one comedy comic in Line Webtoon. The comic contains four panels in each episode, and its stories concern social phenomena. However, the readers said that Tahilalats comic was difficult to understand. This was the reason the writer conducted this study, which was an analysis of the use of the cooperative principle in Tahilalats comic. The study aimed at finding the  forms  of  conversational  implicature  and  describing  the  functions  of conversational  implicature  in  the  comic.  This  study  was  focused  on  30 episodes of the comic, and to collect the data the writer used simak and catat techniques  (Sudaryanto,  1993).  The  results  are  related  to  the  cooperative principle and the conversational implicature. The violation or compliance of the cooperative principles can describe the implicatures in the conversation. The uses of both produce humorous effects because these potentially lead the reader to misunderstand the comic when reading explicitly. However, reading the comic further, the reader will understand the implicit meanings.